Antibacterial Activity of Origanum Syriacum L. Essential Oil against Some Pathogenic Bacteria (Latakia University Journal -Biological Sciences Series, 2013)
In the present study, essential oil taken from the leaves of Origanum syriacum L. (Lamiaceae) growing in Al-Basset mountain forests was obtained by a steam distillation method. The antibacterial activities of the essential oil were also tested on 11 pathogenic bacteria using the Agar well diffusion method.The results showed that the oil has antibacterial activities on all isolated pathogenic Gram positive and Gram negative bacteria at low concentrations: (2-5-10) ml/well. These activities were better than some antibiotics that are used as control at high concentrations (25-30) mg/disc. The results also showed that the inhibition zones greatly increased with the increase of oil concentration three folds or more from 2 to 20 ml/well. .Given these results, it is possible to say that the essential oil taken from the leaves of Origanum syriacum L. has high antibacterial activities against broad spectrum of pathogenic bacteria.